The stages of clinical laboratory diagnostics development at scientific and research institute of children’s infections - L. A. Alekseeva; L. V. Govorova; G. F. Zheleznikova (Журнал инфектологии, 2014)
The article presents the information on the basic stages and directions of clinical laboratory diagnostics development for 85 years of Scientific and Research Institute of Children’s Infections existence. The importance of biochemical and immunological research in the investigation of pathogenesis and working out of new diagnostic criteria to improve the course and possible outcomes of an infectious disease in children is underlined. The emphasis is made on the importance of modern hi-technology equipment usage in carrying out scientific and practical laboratory research.